Analysis of Mathematical Instruction Barriers in Terms of Developing Students' Mathematical Reasoning - Rahma Nasir; Uncok Manigor Jokkas Siahaan; Rayinda Aseti Prafianti (Universitas Islam Lamongan, 2023)
This study aims to analyze the difficulty of teachers in implementing learning that focuses on improving students' mathematical reasoning abilities. The study was a descriptive study. Data were collected via an online form that included open-ended questions. Data were collected from 93 mathematics teachers. Data were analyzed by coding qualitative data using spreadsheet in Microsoft Excel. The categories were derived from the participants’ own words or phrases. The results showed that 81.2 percent of respondents stated that the difficulty teachers experience to improve students' mathematical reasoning abilities is the lack of motivation and disengagement of students and other difficulties. This research also presents alternative solutions that can be practiced by teachers in their respective classes.